On the Margins of Empire : Buraku and Korean Identity in Prewar and Wartime Japan - Bayliss, Jeffrey Paul, 1965- (Book collections on Project MUSE., 2013)
"Provides new insights into the majority prejudices, social and political movements, and state policies that influenced the perceived positions of Koreans and Burakumin as "others" on the margins of the Japanese empire and also the minorities' views of themselves, their place in the nation, and the often strained relations between the two groups"--Provided by publisher